The genesis of end need for country vulnerability profiles - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
The need for country vulnerability profiles is linked to the difficulty of capturing in a single index, no matter how complex, the various kinds of vulnerability which developing countries may face. The Multidimensional Vulnerability Index (MVI) being developed by the United Nations has not removed the need for vulnerability profiles, but rather has brought them back into focus.
Keywords: 330